The effect of ionic strength on DNA-ligand unwinding angles for acridine and quinoline derivatives. - Jones, R L (1980)
We have quantitatively examined the unwinding angles for the complexes of a related series of acridine and quinoline derivatives with DNA. Ethidium bromide was used as a control for determining superhelix densities at different ionic strengths. Relative to ethidium, 9-aminoacridine and quinacrine had an essentially constant unwinding angle of approximately 17 degrees at all ionic strengths tested. The apparent unwinding angle for chloroquine and 9-amino-1,2,3,4-tetrahydroacridine was found to be ionic strength dependent, increasing with increasing ionic strength. This suggests that competitive nonintercalative binding at low ionic strengths causes an apparent lowering of the quinoline unwinding angle. This can also explain why 4-aminoquinaldine, examined at low ionic strength, gives a quite low apparent unwinding angle. Quinacrine along with chloroquinine and 9-aminoacridine approaches a limiting value for their unwinding angle of approximately 17 degrees. 4-aminoquinaldine and 9-amino-1,2,3,4-tetrahydroacridine could not be examined at an ionic strength above 0.03 because of their very low equilibrium binding constants.